Human parainfluenza 3 and respiratory syncytial viruses detected in pangolins. Issue 1 (31st December 2022) - Que, Tengcheng; Li, Jing; He, Yugan; Chen, Panyu; Lin, Wei; He, Meihong; Yu, Lei; Wu, Aiqiong; Tan, Luohao; Li, Yingjiao; Hu, Yanling; Tong, Yigang
ABSTRACT: Pangolins have gained increasing global attention owing to their public health significance as potential zoonotic hosts since the identification of SARS-CoV-2-related viruses in them. Moreover, these animals could carry other respiratory viruses. In this study, we investigated the virome composition of 16 pangolins that died in 2018 with symptoms of pneumonia using metagenomic approaches. A total of eight whole virus sequences belonging to the Paramyxoviridae or Pneumoviridae families were identified, including one human parainfluenza virus 3, one human respiratory syncytial virus A, and six human respiratory syncytial virus B. All of these sequences showed more than 99% nucleotide identity with the virus isolated from humans at the whole-genome level and clustered with human viruses in the phylogenetic tree. Our findings provide evidence that pangolins are susceptible to HPIV3 and HRSV infection. Therefore, public awareness of the threat of pangolin-borne pathogens is essential to stop their human consumption and to prevent zoonotic viral transmission.